2017
DOI: 10.12968/johv.2017.5.3.126
|View full text |Cite
|
Sign up to set email alerts
|

Engaging fathers: Acknowledging the barriers

Abstract: E mental health and development. B attainment, social competence, positive self-esteem and reduced incidence of emotional and behavioural problems. However, the barriers to father-inclusive practice are real and numerous and include personal, organisational, strategic and societal factors. This article reviews the need to work more closely and fruitfully with fathers, and acknowledges some of the barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Potentially, partners may be well placed to help women assess their mental health and, where needed, seek help directly. This supports the idea that care should be family-centred to meet the needs of the woman, her partner and their baby (Bateson et al, 2017).…”
Section: Familysupporting
confidence: 60%
“…Potentially, partners may be well placed to help women assess their mental health and, where needed, seek help directly. This supports the idea that care should be family-centred to meet the needs of the woman, her partner and their baby (Bateson et al, 2017).…”
Section: Familysupporting
confidence: 60%
“…Based on the continuum of family‐focused activities (Leonard et al, ), health visitors engaged in low levels of FFP. As previously discussed, while, partners should be directly supported by health visitors (DOHSS&PS, ), others have also found that ‘the family’ is often mistakenly interpreted as the mother–infant dyad (Baldwin, ; Bateson et al, ; Humphries & Nolan, ). At the centre of FFP is the concept of family and the way health visitors conceptualize the family and roles of members in it influences their FFP.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of this study suggest that health visitors' perceptions of the family were based on stereotypical gender roles, such as fathers as the bread winners and mothers as carers, which led to them viewing partner's needs as secondary to that of mothers and children. Having a female‐centric health visiting system has been suggested to reinforce the feminine nature of care (Bateson et al, ; Page & Whitting, ). Therefore, if health visitors' FFP is to move beyond the mother–infant dyad to encompass partners, their conceptualization of the family and fathers' roles must be challenged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These comments suggest a gap between FCC theory and father inclusive practice; Health Visitors are now acknowledging the gaps in evidence and barriers to effecting inclusivity (Bateson, et al, 2017).…”
Section: Theme Prevention Better Than Curementioning
confidence: 99%